2013
DOI: 10.1093/eurheartj/ehs487
|View full text |Cite
|
Sign up to set email alerts
|

Circulating angiopoietins and cardiovascular mortality in cardiogenic shock

Abstract: Circulating Angs are closely related to outcome and severity in CS. Angiopoietin-2 emerged as an independent predictor of 28-day and 1-year mortality in CS. Larger studies are required to define the cut-off and predictive values for Ang-2. Angiopoietins may be prognostic biomarkers for survival in CS and might represent a novel therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 45 publications
5
39
0
Order By: Relevance
“…However, this difference was much more pronounced and reached statistical significance only at the time of discharge. This finding is consistent with other investigations, which have also shown an association between the mortality and Ang-2 levels measured over time [13,17,23]. Importantly, we found a significant difference regarding the course of Ang-2 concentrations between admission and discharge with respect to mortality.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, this difference was much more pronounced and reached statistical significance only at the time of discharge. This finding is consistent with other investigations, which have also shown an association between the mortality and Ang-2 levels measured over time [13,17,23]. Importantly, we found a significant difference regarding the course of Ang-2 concentrations between admission and discharge with respect to mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Its mediator Ang-2 promotes vascular leakage [5] and could be involved in oedema formation. In previous studies, we have shown a prognostic impact of Ang-2 in patients with cardiogenic shock (CS) [17]. Herein, we show that this also holds true for patients with ADHF.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations